Semiconductor driver of pyroelectric accelerator of charged particles - Ivashchuk, O.O.; Shchagin, A.V.; Kubankin, A.S.; Ionidi, V.Yu; Chepurnov, A.S. (Вопросы атомной науки и техники, 2019)
The possibility for application of semiconductor element for heating of pyroelectric crystalin a pyroelectric ac- celerator of charged particles or pyroelectric X-ray generator is at first proposed and demonstrated experimentally. Spectra of X-ray radiation measured at the heating of the pyroelectric crystal LiNbO₃ by silicon diode at different pressures of residual gas are presented. Perspectives for application of semiconductor heater in the pyroelectric accelerators and X-ray generators are discussed.